Research on Fatigue Properties of Typical Welded Joints of DH36 Steel at −60 °C - Weidong Zhao; Guoqing Feng; Wenchao Liu; Huilong Ren (Applied Sciences, 2020)
As the development of the polar region continues to increase, the fatigue properties of structures at low temperature are increasingly receiving researcher attention. This study aimed to investigate the fatigue properties of T-welded and cruciform welded joints at −60 °C. Logarithmic S–N curves based on the hot-spot stress of the T-welded and cruciform welded joints at 50% and 95% confidence levels were obtained at −60 °C. The test results showed that the fatigue properties of T-welded joints were almost 2–7% better than those of the cruciform welded joints at −60 °C. Factors that affected the fatigue properties of welded joints, such as the stress concentration factor, microstructure, Vickers hardness profiles, and fractography, were also studied and the test results showed that the fatigue properties of cruciform welded joints at −60 °C were 57.215% better than at room temperature.